Altered resting‐state hippocampal functional connectivity in breast cancer survivors with chemotherapy‐induced amenorrhea - Yingying Zhuang; Lili Guo; Wei Huang; Genji Bo; Jiandong Zhang; Zhaohuan Zhu; Yun Feng (Brain and Behavior, 2023)
Abstract Introduction Amenorrhea induced decrease of hormones is associated with cognitive impairment. This study aimed to evaluate hippocampal functional connectivity patterns in chemotherapy‐induced amenorrhea (CIA) breast cancer (BC) patients, to evaluate the relationship between the functional connectivity features and hormone levels. Method Neuropsychological test, functional magnetic resonance imaging, and assessment of hormone levels were conducted in 21 premenopausal BC patients before chemotherapy (t0) and 1 week after completing chemotherapy (t1). Twenty matched healthy controls (HC) were also included and underwent the same assessments at similar time intervals. Mixed effect analysis and paired t‐test were used to compare differences in brain functional connectivity. Results Voxel‐based paired t‐tests revealed increased functional connectivity of the right and left hippocampus with the left fusiform gyrus, inferior and middle temporal gyrus, inferior occipital gyrus, left lingual gyrus, and parahippocampal gyrus after chemotherapy (p < .001) in CIA patients. Repeated measures analysis revealed significant group‐by‐time interactions in the left hippocampus with the bilateral fusiform gyrus, right parahippocampal gyrus, left inferior temporal gyrus, and left inferior occipital gyrus (p < .001). Premenopausal BC patients had no significant differences in cognitive function compared with HC at baseline. However, the CIA patients had high levels of self‐rating depression scale, self‐rating anxiety scale, total cholesterol, and triglycerides. Further, the CIA patients showed significant differences in hormone and fasting plasma glucose levels and cognitive performances between t0 and t1 (p < .05). Functional connectivity changes between the left hippocampus and the left inferior occipital gyrus was negatively correlated with E2 and luteinizing hormone changes (p < .05). Conclusion The CIA patients had cognitive dysfunction mainly in memory and visual mobility. Chemotherapy may affect hippocampal‐posterior cortical circuit which mediates visual processing in CIA patients. Moreover, E2 may be involved in this process.